2024
DOI: 10.2147/jmdh.s459946
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Application of Artificial Intelligence in Nursing Care: Where are We, and What’s Next?

Suebsarn Ruksakulpiwat,
Sutthinee Thorngthip,
Atsadaporn Niyomyart
et al.

Abstract: Background Integrating Artificial Intelligence (AI) into healthcare has transformed the landscape of patient care and healthcare delivery. Despite this, there remains a notable gap in the existing literature synthesizing the comprehensive understanding of AI’s utilization in nursing care. Objective This systematic review aims to synthesize the available evidence to comprehensively understand the application of AI in nursing care. Methods Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Secondly, you mentioned that the data collected in this study were based on self-reported measures, which may introduce reporting bias. 3 Participants may provide answers that do not accurately reflect their true understanding or attitudes toward artificial intelligence (AI). We strongly agree with this point.…”
Section: Dear Editormentioning
confidence: 99%
“…Secondly, you mentioned that the data collected in this study were based on self-reported measures, which may introduce reporting bias. 3 Participants may provide answers that do not accurately reflect their true understanding or attitudes toward artificial intelligence (AI). We strongly agree with this point.…”
Section: Dear Editormentioning
confidence: 99%
“…Participants may provide answers that do not accurately reflect their true understanding or attitudes toward AI. 4 To address this limitation, future research can include objective evaluations of participants’ understanding of AI and attitudes toward AI, rather than relying solely on self-reported measures. 3) The convenience sampling technique used in this study may limit the generalizability of the results to a broader population of medical students.…”
Section: Dear Editormentioning
confidence: 99%